ANALISIS DISIPLIN KERJA PEGAWAI NON ASN PADA SATUAN PELAYANAN PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA DI KECAMATAN PANGKALAN - Ruslan Arosid; Budi Rismayadi; Wike Pertiwi (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the level of employee work discipline and to identify factors that influence employee work discipline at the Population Control and Family Planning Service Unit in Pangkalan District. This study uses a qualitative descriptive methodology, with data collection through observation, interviews, and documentation. There were five informants in this study. Source triangulation is a method for validating data to ensure the credibility of research results. The results show that employee work discipline in Population Control and Family Planning is generally quite good. However, there are still employees who arrive late due to reasons unrelated to work. In addition, work facilities and equipment are utilized well to support the smooth running of tasks, and employees feel that the available facilities are adequate. In terms of responsibility, employees generally perform their duties well. This condition shows that the utilization of facilities and work responsibilities are quite effective, but punctuality needs to be strengthened through more consistent supervision and supporting policies such as providing incentives for disciplined employees so that work discipline can improve comprehensively and sustainably. Further research is recommended to be conducted in agencies or work units with a larger number of employees.